Sistem Informasi Penjualan Kosmetik - Vivin Antika; Emmy Wahyuningtyas (Informatics Engineering Department-UWKS, 2020)
Web-based Cosmetic Sales Information System is an information system that provides or sells cosmetic products. However, many websites only sell cosmetics but do not meet the needs of consumers. Even though there is a cosmetics sales information system, consumers continue to attend seminars or classes held offline by the organizer to increase knowledge about cosmetics. This study aims to create a Sales Information System that can solve the constraints experienced by consumers. These system needs include consumers being able to take part in online seminars, being able to interact with fellow consumers through cyberspace and consumers being able to take beauty classes online. The results of this study are Cosmetic Sales Information Systems which include sales catalogs, online seminar features, online beauty class features, online discussion forum features, and payments.